Potensi Reproduksi dan Distribusi dalam Pengembangan Kambing PE di Desa Hegarmanah Kecamatan Cicantayan Kabupaten Sukabumi Jawa Barat - A Sukendar; M Duldjaman; A Sukmawati (Media Peternakan, 2005)
The study on population dynamic of Etawah crossed goats was carried out in Hegarmanah Village, Sukabumi, West Java. Thirty famers were reviewed and their animals consisted of 52 adult does, 10 adult bucks, 21 young does, 24 young bucks and 58 kids (31 males, 27 females), were studied. Goats were housed continuously. The result showed that the average age of weaning was 5,22 months and weaning weight was 17,63 kg. The age of first matings were 9,83 month for bucks and 7,50 months for does. First kidding was 12,52 months of age and dry period was 5,20 months. Prolificacy was 1,83 kids per does. Litter size was 29,78% singles, 61,70% twins, 4,26% triplets and 4,20% quadruplets. Kidding intervals were 10,20 months. Kid mortality was 9,30%. The population increased 53,70% during six years. Key words: Etawah crossbreed goats, dynamic population, reproduction